Current Challenges in Hepatitis C - Ahad, M Abdul (TAJ: Journal of Teachers Association, 2009)
Hepatitis C is a significant global problem with a wide-ranging personal, social and economic impact. The virus can silently attack the liver for decades before the illness becomes obvious, often as cirrhosis, liver cancer or liver failure. Hepatitis C virus (HCV) is emerging as one of the major health problems in Bangladesh. doi: 10.3329/taj.v21i1.3229 TAJ 2008; 21(1):93-96